PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2014-2016) - Fadhilla, Riska; Rasuli, M; Rofika, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to determine the effect of corporate governance, firm size, and tax avoidance to the acceptance of tax avoidance. The samples of this research are manufacturing companies which listed on the Indonesia Stock Exchange (BEI) in 2014 to 2016. The population of this research are 27 companies. Based on purposive sampling method, the total of final samples are 81 samples. Analysis of data is carried out using multiple regression method with the aid of SPPS version 23 computer program. The result of this research show that managerial ownership, independent board of commissioners, audit committee, and corporate social responsibility are influence on tax avoidance. While institusional ownership and firm size has no effect on tax avoidance.Keywords : managerial ownership, institusional ownership, independent board of commisioners, audit committee, firm size, corporate social responsibility, and tax avoidance.